1992
DOI: 10.1104/pp.98.3.1163
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose Synthase in Wild Tomato, Lycopersicon chmielewskii, and Tomato Fruit Sink Strength

Abstract: Here it is reported that sucrose synthase can be readily measured

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(88 citation statements)
references
References 29 publications
4
82
0
2
Order By: Relevance
“…Since (1) ripening fruits of the domesticated tomato contain higher SI and Susy activities than fruits of the wild types and (2) both enzymes, Susy and SI, are distributed throughout the entire fruit body, we conclude that both enzymes are at least partly responsible for the diVerences in carbohydrate composition of the domesticated tomato fruits and the fruits of the wild types. The present results are in line with previous work on fruits of a wide variety of tomatoes (Yelle et al1988;Miron and SchaVer 1991;Stommel 1992;Sun et al 1992). …”
Section: Carbohydrate Contentssupporting
confidence: 94%
See 1 more Smart Citation
“…Since (1) ripening fruits of the domesticated tomato contain higher SI and Susy activities than fruits of the wild types and (2) both enzymes, Susy and SI, are distributed throughout the entire fruit body, we conclude that both enzymes are at least partly responsible for the diVerences in carbohydrate composition of the domesticated tomato fruits and the fruits of the wild types. The present results are in line with previous work on fruits of a wide variety of tomatoes (Yelle et al1988;Miron and SchaVer 1991;Stommel 1992;Sun et al 1992). …”
Section: Carbohydrate Contentssupporting
confidence: 94%
“…We have initiated a comparative study of developmental changes in the initial steps in carbohydrate metabolism during early fruit development in the S. lycopersicum cv Money Maker and the wild accessions S. peruvianum LA0385 and S. habrochaites LA1777. DiVerences between accessions have been described before but concern only the activity of a limited number of enzymes, e.g., invertase and sucrose synthase (Yelle et al 1988;Miron and SchaVer 1991;Sun et al 1992;Stommel 1992;Balibrea et al 2003). We describe not only the enzymes involved in sucrose breakdown but the next steps in carbohydrate metabolism as well.…”
Section: Introductionmentioning
confidence: 99%
“…At this time starch accounts for 20% of the total dry matter. Sun et al (1992) reported that, using the appropriate extraction method, sucrose synthase activity was readily measured and that sucrose synthase activity per growing fruit was linearly related to final fruit size. Robinson et al (1988) observed a positive correlation between the levels of sucrose synthase activity and starch content in tomato fruit of three varieties (cv 1563, cv VF 145-7879, and cv UC-82B) that differ in starch accumulation in fruit 20 to 40 DAA and in soluble sugars at ripening.…”
Section: Discussionmentioning
confidence: 99%
“…Both acid invertase and sucrose synthase have been implicated as playing a major role in cleaving imported sucrose, which in turn may regulate the rate of carbon import to developing tomato fruit (Walker and Ho, 1977;Johnson et al, 1988;Robinson et al, 1988;Sun et al, 1992). Thus, the relative roles of invertase and sucrose synthase in the determination of tomato fruit sink strength and their relationship with fruit growth are still not understood.…”
Section: Educacion Y Ciencia (Spain)mentioning
confidence: 99%
“…Sun et al (1992) studied fruit sucrose metabolism in L. chmielewskii. As a result, the ability to degrade sucrose does not increase in the latter stage of fruit growth and found that, along with fruit growth and development, AI always maintained a low level of activity, leading to sucrose accumulation in the fruit.…”
Section: Relative Expression Levels Of Tomato Sucrose Invertases and mentioning
confidence: 99%